The New National Health Service - Great Britain. Central Office of Information ([London] : Ministry of Health, 1948)
1948 1948 1940s 1 folded sheet (4 pages) [image] THE NEW NATIONAL HEALTH SERVICE Your new National Health Service begins on 5th July. What is it? How do you get it? It will provide you with all medical, dental, and nursing care. Everyone — rich or poor, man, woman or child — can use it or any part of it. There are no charges, except for a few special items. There are no insurance qualifications. But it is not a "charity". You are all paying for it, mainly as taxpayers, and it will relieve your money worries in time of illness. 21/1974